Study of maximum phonation time and S/Z ratio in laryngeal paralysis - M. S., Sudhakar Rao; Koripalli, Keerthi; P., Apoorva; Malipatil, Vijayalaxmi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Alterations in human voice occur frequently and patients usually complain of hoarseness of voice. Laryngeal paralysis is an important differential diagnosis in patients complaining change of voice. Because of simplicity and ease, maximum phonation time (MPT) and S/Z ratio have become the most frequently used clinical tools to assess phonatory mechanics. Published research studying analysis of MPT and S/Z ratio in patients with vocal cord paralysis (VCP) is scanty. Hence this study was taken up to study MPT and S/Z ratios in patients with laryngeal paralysis. Methods: 62 patients with VCP were included in our study. Complete history was taken and examination was done in all patients. VCP was confirmed by indirect laryngoscopic examination. The MPT and S/Z ratios were evaluated in a quiet room. Data was analyzed using IBM SPSS Version 22. Results: Mean MPT in males with VCP was 6.71±0.54 and in females it was 6.80±2. Mean S/Z ratio in males was 1.69±0.54, in females 1.59±0.35. The difference between laterality of VCP and MPT was statistically highly significant and the difference between laterality of VCP and S/Z ratio was also statistically highly significant. Our study shows no statistically significant difference in MPT and S/Z ratio with respect to age and gender. There was a significant negative correlation between MPT and S/Z ratio. Conclusions: Irrespective of age and gender MPT and S/Z ratio are simple and effective objective clinical tests to diagnose paralytic laryngeal pathologies. As laryngeal pathology heals on treatment MPT and S/Z ratio are expected to normalize indicating therapeutic progress.